2018
DOI: 10.1088/1674-1137/42/3/033103
|View full text |Cite
|
Sign up to set email alerts
|

Search for W′ signal in single top quark production at the LHC

Abstract: Heavy charged gauge bosons are proposed in some theories beyond the standard model.We explore the discovery potential for W ′ → tb with top quark semi-leptonic decay at the LHC. We concentrate on the new physics signal search with the deviation from the standard model prediction if the resonance peak of W ′ cannot be observed directly. Signal events with two jets plus one charged lepton and missing energy are simulated, together with the dominant standard model backgrounds. In this paper, it is found that suit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…An analogous Endo-A mutant, Endo-A N171A, was also created, which could transglycosylate Man9GlcNAc oxazoline effectively. 60 Kinetic studies revealed that the dramatically enhanced synthetic efficiency of the Endo-A N171A mutant over the wild-type Endo-A was due to its significantly reduced hydrolytic activity toward both the Man9GlcNAc oxazoline and the product, as well as to its enhanced activity for transglycosylation. Extension of the chemoenzymatic method to the synthesis of homogeneous glycoforms of ribonuclease B carrying full-size natural N-glycans was achieved (Scheme 9).…”
Section: Generation Of Engase-based Glycosynthases For Transglycosylamentioning
confidence: 99%
See 3 more Smart Citations
“…An analogous Endo-A mutant, Endo-A N171A, was also created, which could transglycosylate Man9GlcNAc oxazoline effectively. 60 Kinetic studies revealed that the dramatically enhanced synthetic efficiency of the Endo-A N171A mutant over the wild-type Endo-A was due to its significantly reduced hydrolytic activity toward both the Man9GlcNAc oxazoline and the product, as well as to its enhanced activity for transglycosylation. Extension of the chemoenzymatic method to the synthesis of homogeneous glycoforms of ribonuclease B carrying full-size natural N-glycans was achieved (Scheme 9).…”
Section: Generation Of Engase-based Glycosynthases For Transglycosylamentioning
confidence: 99%
“…Moreover, the invention of glycosynthases, a class of novel glycosidase mutants that are devoid of hydrolytic activity but are capable of using a suitable activated glycosyl donor for transglycosylation, provides a beautiful solution to the two fundamental problems associated with glycosidase-catalyzed synthesis: the low transglycosylation efficiency and product hydrolysis. 32,[57][58][59][60][61][62][63][64] On the other hand, recent advances have shown that both glycosyltransferases and glycosidases can in fact have relaxed substrate specificity, allowing the synthesis of both natural and selectively modified complex carbohydrates. 25,56 In this chapter, we highlight recent advances in the use of endoglycosidases for the synthesis of biologically interesting glycans and glycoconjugates, including natural and artificial polysaccharides, glycoproteins, and glycolipids.…”
Section: Enzymes As a Tool For The Synthesis Of Glycans And Glycoconjmentioning
confidence: 99%
See 2 more Smart Citations
“…In single top quark production, the produced top is highly polarised allowing for a direct test of the V − A structure of weak interaction [11]. Finally, single top production is one of the interesting channels to look for new physics beyond the Standard Model [12][13][14][15]. Extensive studies of single top production at hadron colliders including radiative corrections have been performed at NLO [16][17][18][19][20][21][22][23][24] and NNLO [25][26][27] in the strong coupling.…”
Section: Introductionmentioning
confidence: 99%